Impairment of Drosophila orthologs of the human orphan protein C19orf12 induces bang sensitivity and neurodegeneration. - Arcangela Iuso; Ody C M Sibon; Matteo Gorza; Katharina Heim; Cristina Organisti; Thomas Meitinger; Holger Prokisch (PLoS ONE)
Mutations in the orphan gene C19orf12 were identified as a genetic cause in a subgroup of patients with NBIA, a neurodegenerative disorder characterized by deposits of iron in the basal ganglia. C19orf12 was shown to be localized in mitochondria, however, nothing is known about its activity and no functional link exists to the clinical phenotype of the patients. This situation led us to investigate the effects of C19orf12 down-regulation in the model organism Drosophila melanogaster. Two genes are present in D. melanogaster, which are orthologs of C19orf12, CG3740 and CG11671. Here we provide evidence that transgenic flies with impaired C19orf12 homologs reflect the neurodegenerative phenotype and represent a valid tool to further analyze the pathomechanism in C19orf12-associated NBIA.